If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1x + 3) + -5 = 9 Reorder the terms: 2(3 + -1x) + -5 = 9 (3 * 2 + -1x * 2) + -5 = 9 (6 + -2x) + -5 = 9 Reorder the terms: 6 + -5 + -2x = 9 Combine like terms: 6 + -5 = 1 1 + -2x = 9 Solving 1 + -2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 9 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 9 + -1 -2x = 9 + -1 Combine like terms: 9 + -1 = 8 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| 39/949 | | 3(8x-1)+7(x+5)=-59 | | 9=-6w+3(w-6) | | 4=12-d | | 15k=k-2 | | -7.6=0.4-4y | | 5x*5=180 | | 2.3x=12 | | 22=4(y+8)-6y | | -7/8x=49 | | -15r=r-7 | | -2+15+x=-4+8 | | 11x+66=21 | | 12=9-c | | 5x+2x+6x= | | 4(n+2)+3(2n+6)= | | 75+64+x=180 | | 7=3m+1 | | 2y+3y=30x | | a(2ab-5c)= | | 2x+y-3x=1 | | 2x-3(-2x+22)=-130 | | 3j+4=10 | | 201=17b+99 | | 6=2-b | | 3(-2-3x)=9x | | 20x+240=240 | | 33x-8-14x=10 | | 8x-8=15x-21 | | 2d+18=2-6(d+7) | | =8.041840047611249e+17 | | 5=1-a |